Squares: Supporting Interactive Performance Analysis for Multiclass Classifiers - Ren, Donghao; Amershi, Saleema; Lee, Bongshin; Suh, Jina; Williams, Jason (IEEE TVCG, VAST, 2016)
Performance analysis is critical in applied machine learning because it influences the models practitioners produce. Current performance analysis tools suffer from issues including obscuring important characteristics of model behavior and dissociating performance from data. In this work, we present Squares, a performance visualization for multiclass classification problems. Squares supports estimating common performance metrics while displaying instance-level distribution information necessary for helping practitioners prioritize efforts and access data. Our controlled study shows that practitioners can assess performance significantly faster and more accurately with Squares than a confusion matrix, a common performance analysis tool in machine learning.